2016
DOI: 10.1038/nm.4133
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the reward system boosts innate and adaptive immunity

Abstract: Positive expectations contribute to the clinical benefits of the placebo effect. Such positive expectations are mediated by the brain's reward system; however, it remains unknown whether and how reward system activation affects the body's physiology and, specifically, immunity. Here we show that activation of the ventral tegmental area (VTA), a key component of the reward system, strengthens immunological host defense. We used 'designer receptors exclusively activated by designer drugs' (DREADDs) to directly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(127 citation statements)
references
References 37 publications
2
124
0
1
Order By: Relevance
“…Stress-induced alterations of the immune response is now extensively documented and is known to rely on two main pathways: the hypothalamus-pituitary-adrenal axis and the autonomic nervous system (ASN) pathway 202, 203 . Recently, the brain reward system was also shown to deeply impact immune responses via signaling through the ASN 204 . CNS-derived superautoantigens and their instructing roles on immune repertoires could thus provide another mechanism of brain-induced immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Stress-induced alterations of the immune response is now extensively documented and is known to rely on two main pathways: the hypothalamus-pituitary-adrenal axis and the autonomic nervous system (ASN) pathway 202, 203 . Recently, the brain reward system was also shown to deeply impact immune responses via signaling through the ASN 204 . CNS-derived superautoantigens and their instructing roles on immune repertoires could thus provide another mechanism of brain-induced immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are mediated through central mAChRs and the vagus nerve. A recent study highlighted the involvement of dopaminergic signaling in the regulation of peripheral immune function (145). Selective chemogenetic stimulation of dopaminergic receptors in the ventral tegmental area results in augmented macrophage and dendritic cell phagocytic activity, macrophage and monocyte bactericidal activation, and suppressed bacterial accumulation in the liver (145).…”
Section: The Role Of the Central Nervous Systemmentioning
confidence: 99%
“…A recent study highlighted the involvement of dopaminergic signaling in the regulation of peripheral immune function (145). Selective chemogenetic stimulation of dopaminergic receptors in the ventral tegmental area results in augmented macrophage and dendritic cell phagocytic activity, macrophage and monocyte bactericidal activation, and suppressed bacterial accumulation in the liver (145). These effects are abrogated in animals with disrupted sympathetic catecholaminergic neurons, pointing to their mediating role in enhancing antibacterial immune activation (145).…”
Section: The Role Of the Central Nervous Systemmentioning
confidence: 99%
“…In a blinded study, researchers found that 28 of 34 epileptic dogs responded to placebo treatment (Munana, Zhang, & Patterson, 2010). Research further documents a range of placebo phenomena in non-human animals for a spectrum of objective measures, including antibody production (Ader, Kelly, Moynihan, Grota, & Cohen, 1993;Jaeger, Larsen, & Moe, 2006;McMillan, 1999) and bacterial immunity (Ben-Shaanan et al, 2016).…”
Section: Animals Respond To Eeg-nf But Do Not Respond To Placebosmentioning
confidence: 99%